2008
DOI: 10.1007/s12199-008-0049-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term study of urinary bisphenol A in elementary school children

Abstract: Objectives Due to its industrial application and frequent use as a coating material for food containers, bisphenol A (4,4 0 -isopropylidenediphenol, BPA) is present in abundance in our environment. Data on intake levels of BPA are limited in preadolescent children in Japan. This study was designed to help us better understand the current state of BPA exposure in children in Japan. Methods We followed first graders (n = 104) attending school in a Tokyo suburb from 1998 until the sixth grade (2003), during which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Urinary BPA concentrations measured at 9 years of age were positively associated with BMI, WC, fat mass, and overweight/obesity in both boys and girls. 140 Contrary to these findings, in a different cohort, Yamano et al 141 found that after a five year follow-up, urinary BPA measurements had no association with BMI. Similar results were seen in other crosssectional studies where older children had higher BPA concentrations that correlated to an increased risk of being overweight/ obese, specifically in females.…”
Section: Metalsmentioning
confidence: 90%
“…Urinary BPA concentrations measured at 9 years of age were positively associated with BMI, WC, fat mass, and overweight/obesity in both boys and girls. 140 Contrary to these findings, in a different cohort, Yamano et al 141 found that after a five year follow-up, urinary BPA measurements had no association with BMI. Similar results were seen in other crosssectional studies where older children had higher BPA concentrations that correlated to an increased risk of being overweight/ obese, specifically in females.…”
Section: Metalsmentioning
confidence: 90%
“…Calafat et al documented extensive exposure to the general US population in a subset of the 2003-2004 National Health and Nutrition Examination Survey (NHANES), where 93% of the 2,517 participants had detectable BPA in their urine [6]. Additionally, other studies in the Netherlands [7], Germany [8], China [9], Japan [10], and Norway [11] have all found similar population wide exposure to BPA in each respective country. Human studies have also measured BPA in a variety of other human body fluids and some tissues.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have suggested that the BPA concentration in urine or blood is a biomarker of BPA which remains in the body as a result of the placement of resin‐based dental materials 5,11,13,18,23–25 . The oestrogenic effect of BPA has led to concerns with regard to its negative health effects.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple regression models were built to analyse the association between the numbers of surfaces restored with different types of filling material (resin, sealant and resin composites, which were defined as the combination of the number of resin fillings and sealants in this study) and the creatinine‐adjusted BPA concentration in urine. Regression models were adjusted by gender and age, as age and gender are two factors related to BPA concentrations in the body; however, these factors were not in the causal pathway between resin composite restoration and BPA concentration in urine 12,13,20 . Data analyses were performed using SAS 9.1.3 (SAS Institute, Inc., Cary, NC, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation